Rozmowa o historii misji średniowiecznych - Strzelczyk, Jerzy (Annales Missiologici Posnanienses, 2014)
On September 25-26th 2014 the Institute of History, Adam Mickiewicz University in Poznań, has organized a conference „Christianization of Europe. The Church at the turn of the first and second millenium”. It was the first of planned three conferences which preceed the 1050 anniversary of the baptism received by Polish prince Mieszko I in 966 and the official introduction of Christianity to Poland. Prof. Strzelczyk was one of the main organizers of this conference and the discussion reported below touches the subjects related to his professional career as a historian, focusing on the study of the history of Christian missions in Middle Ages.